Tindak Tutur Ilokusi pada Jual Beli di Pasar Karangpucung Kabupaten Cilacap - Risna Windika Cahyani; Cintya Nurika Irma; Mulasih Mulasih (Institut Agama Islam Negeri Curup, 2021)
The purpose of this study is to describe and analyze the forms of illocutionary speech acts that exist in the buying and selling process at Pasar Karangpucung, Kabupaten Cilacap. This research is a qualitative research with descriptive method. The Data collection technique in this study was the recording technique. Then, the source of the data came from the record obtained in the buying and selling process in the Pasar Karangpucung, Kabupaten Cilacap. The result of the study found five forms of illocutionary speech acts in the form of assertive speech acts, directive speech acts, commissive speech acts, expressive speech acts, and declarative speech acts. The form of speech found in the form of stating, informing, mentioning, indicating, asking, suggesting, imploring, prohibiting, promising, swearing or convincing earnestly, thanking, complaining, apologizing, giving an apology, and the last one creating a new atmosphere or situation